(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Aim: This descriptive type of cross sectional study was conducted with an objective to evaluate the views of doctors regarding knowledge and practices about patient safety working at primary and secondary level health care facilities in Bangladesh. Methods: Study period was from August 2016 to December 2016. Multistage, convenience sampling was done . Sample size was 550. Self administered semi structured questionnaire was used for data collection after pre testing. Data was collected by principle investigator , co-investigator & data collectors. Data was also collected by sending questionnaire by postage followed by a focal group discussion. Results: Result showed 70 % were male and 57% were primary level medical officers. 44.9% understands patients safety. 51.1% understands medical errors . 37.5% agreed that less duty hours will reduce medical errors . 62% strongly agreed that Learning about patient safety will enhance competency. 44.5% agreed that undergraduate course prepared them to ensure patient safety. 37.5 % agreed that they learned about medical errors during their undergraduate course. 40.6% stated that they were assigned to perform the tasks for which they were not trained competently, 34% said that they were assigned to perform the tasks which could have resulted easily in medical errors . Most of the respondents strongly agreed that teaching about patient safety should be an important priority. 46% stated that these should be in clinical teaching and 40% stated the same to be in bed side teaching . 24% stated that there were not enough topics in the existing curriculum regarding patient safety. 46% confessed that they made medical errors during their practices. 33% stated that they want patient safety education in their professional practice, 76.9% strongly agreed that patient safety is an important issue in their professional practices and 44% sensitizes their colleagues about patient safety to learn & practices. 54.7% stated that they did not have error reporting system/ death review/ medical audit in their hospital, 89.7% did not have attended any training on patient safety . 90% thought that training on patient safety is essential for doctors 67.2% respondents opined that there should be a competent organization / body who can take care of patient safety & medical errors in Bangladesh. Conclusion: The study reflects that many primary level medical officers do not understand patients safety and medical errors. The study also showed that most of them has a positive attitude torwards patient safety. Study recommended that doctors serving at primary and secondary level healthcare facilities to be oriented/ trained on different aspects of patient safety J Bangladesh Coll Phys Surg 2020; 38(1): 5-11